Joint symptoms associated with anastrozole and letrozole in patients with breast cancer: a retrospective comparative study - Yoshihito Morimoto; Shuhei Sarumaru; Yuko Oshima; Chiho Tsuruta; Kazuhiro Watanabe (BMC, 2017)
Abstract Background Joint symptoms are a common side effect of aromatase inhibitors. However, it is not known if the risk of these symptoms varies between the members of this drug class. The aim of this study was to compare the frequency of joint symptoms associated with anastrozole and that associated with letrozole. Methods We retrospectively reviewed patients with breast cancer who were treated with anastrozole or letrozole at Tsukiji Breast Clinic, Japan, between April 2008 and July 2014. Joint symptoms were deemed to include both joint pain and painless joint symptoms. The time to onset of joint symptoms in the anastrozole group was compared with that in the letrozole group using Kaplan-Meier curves and the log-rank test. Results Of 141 patients identified to have received aromatase inhibitors, 70 had been treated with anastrozole and 71 with letrozole. Joint symptoms occurred in 60.3% of the 141 patients (60.0% in the anastrozole group and 60.6% in the letrozole group; p = 1). Median time to appearance of joint symptoms was 583 days, with no significant difference between the anastrozole and letrozole groups (p = 0.962). There was no significant difference in time to onset of joint pain (p = 0.139); however, time to onset of painless joint symptoms was significantly shorter in the anastrozole group (p = 0.022). The sites at which joint symptoms occurred were similar in the two groups. Conclusions The results of this study indicate that there is no difference in the pattern of occurrence of joint symptoms caused by anastrozole and those caused by letrozole. Trial registration Trial registration was not required for this study because of its retrospective nature and lack of intervention.